Procedural Justice in Housing: The Impact of Legal Safeguards on Eviction Outcomes for Low-Income Renters - Hermansyah (Indonesian Scientific Publication, 2025)
Housing insecurity and eviction disproportionately impact low-income renters, undermining social and economic stability. This study assesses the effectiveness of procedural legal protections—specifically the right to counsel and the proportionality test—in reducing eviction rates across jurisdictions. Grounded in international human rights frameworks such as the ICESCR and UN-Habitat guidelines, the research investigates whether codified procedural safeguards correspond with lower levels of involuntary displacement. Using a panel Difference-in-Differences (DiD) design, the study analyzes data from the Eviction Lab (U.S.), OECD Affordable Housing Database, and a custom legal protections index. Comparisons were made between jurisdictions with and without procedural safeguards, controlling for unemployment, rent inflation, and urban density. Results show that right-to-counsel statutes significantly reduce eviction filings—by up to 60% in cities like New York and San Francisco (2013–2020). Proportionality tests were also linked to improved housing outcomes, particularly when integrated into broader legal frameworks. Subgroup analyses reveal that informal tenants and racial minorities benefit less unless explicitly covered by law. The effectiveness of these protections depends heavily on enforcement capacity and the availability of legal aid. The study concludes that procedural legal protections are vital policy tools for advancing housing justice. To maximize their impact, legal reforms must extend beyond codification to include inclusive design, public awareness, and strong institutional enforcement. These findings contribute to housing law and social policy by empirically demonstrating the role of legal safeguards in preventing eviction and promoting tenure security.